Diabetes and cancer risk: A Mendelian randomization study - Goto, Atsushi; Yamaji, Taiki; Sawada, Norie; Momozawa, Yukihide; Kamatani, Yoichiro; Kubo, Michiaki; Shimazu, Taichi; Inoue, Manami; Noda, Mitsuhiko; Tsugane, Shoichiro; Iwasaki, Motoki (International journal of cancer, 2020)
Earlier cohort studies using conventional regression models have consistently shown an increased cancer risk among individuals with type 2 diabetes. However, reverse causality and residual confounding due to common risk factors could exist, and it remains unclear whether diabetes per se contributes to cancer development. Mendelian randomization analyses might clarify the true association between diabetes and cancer risk. We conducted a case–cohort study with 10,536 subcohort subjects and 3,541 newly diagnosed cancer cases derived from 32,949 eligible participants aged 40–69 years within the Japan Public Health Center‐based Prospective Study. With 29 known type 2 diabetes susceptibility variants, we used an inverse variance‐weighted method to estimate hazard ratios for the associations of diabetes with risks of total and site‐specific cancers. The hazard ratios of cancer per doubling of the probability of diabetes were 1.03 (95% confidence interval [CI], 0.92–1.15) overall, 1.08 (95% CI: 0.73–1.59) for the pancreas, 0.80 (95% CI: 0.57–1.14) for the liver and 0.90 (95% CI: 0.74–1.10) for the colorectum. Additional analyses, using publicly available large‐scale genome‐wide association study data on colorectal cancer in Japan, resulted in a narrower CI (hazard ratio: 1.00; 95% CI: 0.93–1.07). In this prospective Mendelian randomization study with a large number of incident cancer cases, we found no strong evidence to support associations between diabetes and overall and site‐specific cancer risks. Our findings suggest that there is little evidence to support the genetic role of type 2 diabetes in cancer development in the Japanese population. What's new? While type 2 diabetes is implicated in cancer development, the two conditions share multiple risk factors, raising questions about the actual contribution of diabetes to cancer risk. Here, a Mendelian randomization (MR) analysis was used to clarify the relationship between diabetes and cancer in a Japanese cohort. Based on data for 32,949 individuals, including 3,541 incident cancer cases, MR analysis revealed no strong genetic evidence supporting a link between diabetes and cancer risk, including site‐specific and overall risk. This finding was confirmed by investigation of data from a genome‐wide association study of colorectal cancer from the BioBank Japan Project.